Osmotic pressure induced by extracellular matrix drives Bacillus subtilis biofilms' self-healing. (April 2022) - Dong, Fulin; Liu, Song; Zhang, Duohuai; Zhang, Jinchang; Wang, Xiaoling; Zhao, Hui
Abstract: The formation of bacterial biofilms is due to the bacteria adhering to the contact surface, secreting exopolysaccharide (EPS) and proteins, which make a large number of bacteria aggregate to form communities. In our experiments, we find that biofilms can heal after being destroyed like cut. To understand how biofilms self-heal, we use a diffusion–reaction continuum model to simulate the biofilm self-healing process, by using the extended finite element and level set method through MATLAB. The extended finite element method is used to calculate the diffusion of nutrients and the pressure field in the biofilm during the self-healing process, and the level set method is used to track the biofilm edge expansion and the cutting edge healing. The result can well describe the experimental observation, we find that the cut in the young biofilm heals almost completely, while old biofilms heal only at the edge. According to the phenotype observation, we find that matrix producing cells contribute to the biofilm self-healing, matrix producing cells secrete exopolysaccharide causing the difference of macromolecular substances' concentration in the biofilm and the agar substrate, which results in osmotic pressure promoting the transport of nutrients and leads to cut healing. Our simulation demonstrates that the nutrient concentration and the osmotic pressure are confinements for the biofilm healing. Graphical Abstract: ga1 Highlights: We observe that Bacillus subtilis biofilms can self-heal after being destroyed. We analyze the effects of phenotype and environment on Bacillus subtilis biofilms' self-healing. We use a model to simulate the Bacillus subtilis biofilms self-healing process. We explore the mechanism of Bacillus subtilis biofilms' self-healing.